Botulinum toxin A inhibits salivary secretion of rabbit submandibular gland - Shan, Xiao-Feng (Nature Publishing Group, 2013)
Botulinum toxin A (BTXA) has been used in several clinical trials to treat excessive glandular secretion; however, the precise mechanism of its action on the secretory function of salivary gland has not been fully elucidated. In this study, we aimed to investigate the effect of BTXA on secretion of submandibular gland in rabbits and to identify its mechanism of action on the secretory function of salivary gland. At 12 weeks after injection with 5 units of BTXA, we found a significant decrease in the saliva flow from submandibular glands, while the salivary amylase concentration increased. Morphological analysis revealed reduction in the size of acinar cells with intracellular accumulation of secretory granules that coalesced to form a large ovoid structure. Expression of M3-muscarinic acetylcholine receptor (M3 receptor) and aquaporin-5 (AQP5) mRNA decreased after BTXA treatment, and distribution of AQP5 in the apical membrane was reduced at 1, 2 and 4 weeks after BTXA injection. Furthermore, BTXA injection was found to induce apoptosis of acini. These results indicate that BTXA decreases the fluid secretion of submandibular glands and increases the concentration of amylase in saliva. Decreased expression of M3 receptor and AQP5, inhibition of AQP5 translocation, and cell apoptosis might involve in BTXA-reduced fluid secretion of submandibular glands.